STUDIES ON COMBINING ABILITY OVER ENVIRONMENTS IN HYBRID RICE (Oryza sativa L.) - A.S. HARI PRASAD, K.PARIMALA, CH. SURENDER RAJU and (The Journal of Research, PJTSAU, 2019)
A field investigation was carried out to identify effective restorers and maintainers to use in hybrid rice breeding programme. In this study 36 hybrids were developed by crossing three wild abortive based CMS lines with 12 restorers in line x tester design. The pooled analysis of variance over locations indicated that mean squares due to environments were significant for all the traits except for days to 50% flowering and 1000 grain weight, while crosses exhibited significant differences for all the traits studied. Line x tester effect showed significant differences for the traits studied except for days to 50 % flowering. Specific combining ability variance was higher than the general combining ability variance for the traits studied except for days to 50% flowering. This indicated the predominance of non-additive gene action in controlling these traits. The lines IR-58025A, IR-79156A and the testers RNR-15048, RNR-2781 were found to be good general combiners for most of the yield contributing traits. The testers IR-83142- B-57-B, D-4098 and RNR-15351 exhibited earliness and short stature. The hybrids IR-79156A x NWGR-3132 and IR-79156A x RNR-2456 were found to be good specific combiners over the environments for grain yield per plant, number of productive tillers per plant, panicle length and number of filled grains per panicle. These hybrids could be utilized for exploitation of heterosis for grain yield in hybrid rice.